An Analysis of Students’ Speaking Skill through British Parliamentary Debate System - Ayu Ridha Tami; Wariyati Wariyati; Ahmad Laut Hasibuan (Magister of English language Education study program, Universitas Muslim Nusantara Al Washliyah, 2021)
The purpose of this research was to investigate the students’ speaking skill through British Parliamentary (BP) debate System. This observation was taken 18 Days which started from Thursday, 13th February to 12 March 2020. The Qualitative Research Method was used in this research. The subjects of this research chosen randomly were 8 student as the representative of students in the fourth semester of English education UMN Al Washliyah Medan Class A, academic year 2019-2020. The population from this research were the whole students in the 4th semester English Education Department Class A.Technique of collecting data used was the observation in which the students were observed during debate class by using observation sheet designed with theory of Finocchiaro in Armasita (2017) to know the ability that have been achieved by the students and all the data found from 8 subjects of research that have been analyzed by the researcher there were 4 indicators/elements, namely pronunciation, vocabulary, fluency and comprehension. After the research conducted, it was found that there were 3 students with the higher speaking skill, 4 students with the moderate speaking skill, and only one student categories as the unsatisfied speaking skill. Shortly, this finding of the research was appropriate with the assumption in this research that is debate is effective to increase the students’ speaking skill.